Kebudayaan Suku Bugis: Uang Panai dalam Perspektif Agama Islam - Mardiah, Ainul; Hidayati, Putri Nesya Hilda Dwi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out how Islam views uang Panai` which is one of the cultures in Bugis marriage. In Islamic law, there are 4 conditions for customs to be used as a legal footing. namely: (1). not contrary to one of the nash shari'ah, (2). Valid and enforced in general and constant, (3). The tradition has been established at the time of its implementation, (4). There is no speech or action that contradicts the substantial value contained by the tradition.This research uses a literature study approach. Where the main focus of the discussion of this article is uang panai' in the perspective of Islam. The sub-discussions in this article are explaining the culture of the Bugis tribe, marriage in the Bugis tribe, and uang panai' in the perspective of the Bugis tribe.